Corruption in Police: Changes in Police-Entrepreneur Relations - КравцоваМария Владимировна (Journal of Economic Sociology, 2012)
The article demonstrates that the structure of corruption relations between police officers and small businessmen has been changing. Informal payments have been replaced by forms of corruption relations which do not involve payments but suppose long-term bilateral contracts and mechanisms of tit for tat reciprocity. These transformations influence the entrepreneurial climate in a significant way. The system where the role of personal ties with officials is especially important, some entrepreneurs feel much better. They have less cost loading, understand deeper their interests, and accumulate more resources in order to protect them in dealing with police officers. There are a lot of factors influencing business climate; therefore it is too early to suppose its significant improvement.